1984
DOI: 10.1172/jci111408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketone bodies on glucose production and utilization in the miniature pig.

Abstract: As bstract. The effect of ketone bodies on glucose production (Ra) and utilization (Rd) was investigated in the 24-h starved, conscious unrestrained miniature pig. Infusing Na-DL-3-OH-butyrate (Na-DL-f-OHB) and thus shifting the blood pH from 7.40 to 7.56 resulted in a decrease of Ra by 52% and of Rd by 45%, as determined by the isotope dilution technique. Simultaneously, the concentrations of arterial insulin and glucagon were slightly enhanced, whereas the plasma levels of glucose, lactate, pyruvate, alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 49 publications
(64 reference statements)
5
41
2
1
Order By: Relevance
“…In contrast to a previous study that found increased glucagon concentrations after BHBA infusion in pigs (Müller et al, 1984), in the current study BHBA infusion decreased glucagon concentration in HyperB compared with the control group. Plasma glucose is derived from the feed, glycogen, and by gluconeogenesis, and it is regulated by several hormones, mainly glucagon and insulin.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to a previous study that found increased glucagon concentrations after BHBA infusion in pigs (Müller et al, 1984), in the current study BHBA infusion decreased glucagon concentration in HyperB compared with the control group. Plasma glucose is derived from the feed, glycogen, and by gluconeogenesis, and it is regulated by several hormones, mainly glucagon and insulin.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with other reports of decreased plasma glucose concentration associated with elevated BHBA in pregnant sheep Harmeyer 2003, 2004), dogs (Felts et al, 1964;Madison et al, 1964), and pigs (Müller et al, 1984). However, our findings are in contrast to other reports that described a hyperglycemia in rabbits (Mirsky and Broh-Kahn, 1937) induced by ketone bodies infusion.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations